Hard to learn for the future? Field evidence from a digital-green classroom pilot shows no gains and lower enjoyment - Leonie Dworsky; David Pipke; Juliet Tschank (Kiel Institute for the World Economy (IfW Kiel), 2025)
We evaluate Raise-Up, a pilot in two Turin-area vocational schools that integrated project-based learning on digitization and the green transition into the regular curriculum. Using a difference-indifferences design on three survey waves, we find no positive effects on any pre-registered outcomes, including aspirations, motivation, competencies, preferences, and socio-emotional engagement. The only significant effect is negative: treated students report lower school enjoyment (-0.39σ), plausibly from higher workload. Impacts are more adverse for females, reducing self-confidence and perceived job knowledge, with no socio-economic differences. Post-program feedback aligns with these results, suggesting limited benefits and potential unintended costs.
Keywords: I21; J24; Q59; 330; vocational education and training; digital skills; green skills; projectbased learning; dropout prevention; gender differences; field experiment